Methodological and Theoretical Problems for a New Translation of the Iliad (El Hilo de la Fabula, 2022)
The aim of this article is twofold: to demonstrate the need for a new translation of the Iliad based on an analysis of the available translations characteristics, and to present some strategies for the new translation used in the iliada.com.ar project.The former is achieved by taking into consideration not only the translation criteria used by contemporary authors, on which brief comparative analysis is made, but also the modes of circulation and the methodology of work in these publications. The reached conclusion is that the main deficiency of contemporary translations lies in the non-construction of a specific language to translate the Homeric and, therefore, the second part of the article presents the main strategies used in our project to achieve this goal.
Keywords: Homer; Iliad; translation; epic language; oral poetry